(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the past few years, Vehicular Adhoc Networks (VANETs), known as Vehicle-to-Vehicle and Vehicle-to-Roadside wireless communications, have received a huge amount of well-deserved attention in the literature. Indeed, because of their unmistakable societal impact that promises to revolutionize the way we drive, various car manufacturers, government agencies and standardization bodies have spawned national and international consortia devoted exclusively to VANET. Examples include the Car-2-Car Communication Consortium, the Vehicle Safety Communications Consortium, and Honda’s Advanced Safety Vehicle Program among others. The impetus of VANET is that in the not-so-distant future vehicles equipped with computing, communication and sensing capabilities will be organized into a ubiquitous and pervasive network that can provide numerous services to travelers, ranging from improved driving safety and comfort, to delivering multimedia content on demand, and to other similar value-added service. Indeed, the fact of being networked together promotes car-to-car communications, even between cars that are tens of miles apart.